(untitled) (Italian Journal of Public Health, 2011)
According to WHO, cancer represents a leading cause of death worldwide, accounting for 7.6 million deaths (around 13% of all deaths) in 2008. About 30% of cancer deaths are due to the following behavioral and dietary risks: high body mass index (BMI), low fruit and vegetable intake, lack of physical activity, tobacco and alcohol use. Currently, innovative cancer treatments and therapies are available, but it is important to consider that the burden of cancer can be reduced by implementing evidence-based strategies for cancer prevention, early detection of cancer and management of patients affected by the disease.